Liberation Through Education: Teaching #BlackLivesMatter in Africana Studies - Wallace, Danielle M. (Radical Teacher, 2016)
This paper is based on teaching about #BlackLivesMatter in Africana Studies in two seminar courses during the Spring of 2015 and 2016, respectively. Guided by a pedagogy grounded in the belief that education can be a tool of social justice, arguments are made for how to frame discussions of #BlackLivesMatter in regard to the socio-historical circumstances that inform and shape the modern day movement. In addition, suggestions are made for including a discussion of the tradition of activism within the Black community as a way to understand the present movement.